Management of HCV Positive Patients on Maintenance Dialysis - Samee Ullah Khan, Irfan Elahi, Rizwan Munir Ahmed, Aeliya Batool, Shajia Haider, Oliva Araujo (Pakistan Journal of Medical & Health Sciences, 2023)
The prevalence of hepatitis C virus (HCV) is quite high in Pakistan, especially among patients on maintenance hemodialysis (MHD). HCV infection is associated with increased morbidity and mortality among patients on maintenance hemodialysis. The current availability of direct-acting antiviral therapy has changed the picture of HCV prevalence in many countries. Objective: The aim of our study is to assess the prevalence and treatment of HCV infection among patients on maintenance hemodialysis in our setting. Methods: This descriptive cross-sectional study was held in the Medicine department of Mayo Hospital, Lahore for six-months duration from 13th January 2022 to 12th July 2022. The study was conducted on 130 patients to assess HCV seroprevalence among patients on MHD. Data on HCV status, PCR positivity and number of patients receiving active treatment were evaluated. Results: A total of 130 patients on maintenance hemodialysis were included in this study. The incidence of HCV infection was 49 (37.7%). All patients underwent PCR and 32 patients were PCR positive. All except 5 of the 32 PCR positive patients started HCV antiviral treatment. Conclusions: In conclusion, our study helps highlight the high prevalence of HCV among maintenance hemodialysis patients and the need to maintain adequate infection control measures. However, it is encouraging to know that most patients have been treated, and future research will highlight the importance of prompt treatment for MHD patients. It is recommended that all of HCV PCR positive patients were being treated with DAA. Keywords: HCV, Hemodialysis, Antivirals, Seroconversion, Health insurance, Infection.